Adoption of crossbred cow technologies and increased food security among smallholder dairy farmers in the East African highlands - Ahmed, M.; Ehui, Simeon K.; Mohamed-Saleem, M.A. (Informa UK Limited, 2002)
This study investigates the household-level impacts of market-oriented dairy technologies (crossbred cows and complementary feed and management technologies) on in-comes, food and non-food expenditures, nutrient intakes, and health of pre-school children. A recursive econometric model was employed using detailed household level survey data of production, income and consumption, nutrition, and health. Results show that market-oriented technologies are significant determinants of income. The size of the cultivated area, herd size, and purchased inputs are positively and strongly associated with the level of per capita income. Predicted income has a positive and significant influence on expenditures of food and non-food items. Price of food, however, has a negative and significant impact on expenditures. Results also indicate that womens’ knowledge, expenditure on food, and price of nutrients are important determinants of nutrient intakes. The analysis of the factors affecting the health status revealed that womens’ practice and knowledge, and age of the mother and female headship are important determinants of the weight-for-age and weight for height scores. Also, participation in village level health programs has a significant effect (at 10% level) on the weight for height. The policy implications resulting from this study clearly indicate that strategies that promote market-oriented smallholder dairy can improve food security as it contributes to an increased per capita income, thereby increasing per capita expenditure on food and non-food items. This increase in turn, positively affects the intake of nutrients. Therefore, to improve health, it is useful to focus on the role of woman in the household.